Hubungan Berat Badan Lahir, Panjang Badan Dan ASI Eksklusif Dengan Masalah Stunting Pada Balita Usia 24-59 Bulan Di PMB Bidan S : The Relationship Between Birth Weight, Length and Exclusive Breastfeeding with Stunting Problems in Toddlers Aged 24-59 Months at PMB Midwife S - Purba, Shopia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Stunting One of the nutritional problems faced by Indonesia is stunting. Stunting is very important because it will affect human resources in the future. Many factors cause stunting in toddlers. one of the factors that influence them is birth weight, length, and exclusive breastfeeding. This study aims to determine the relationship between birth weight, birth length, and exclusive breastfeeding with Stunting Incidence in toddlers aged 24-59 months at PMB Midwife S Jakarta in 2022.  Methods: Observational study with a case-control design in toddlers aged 24-59 months at PMB Midwife S Jakarta in 2022. The number of samples included 35 cases and 35 controls. The nutritional status of stunting toddlers is categorized based on height for age with a z-score (<-2SD). Height data was measured using a microtome. Data on birth weight and birth length were seen from the MCH book. Exclusive breastfeeding data were obtained using a questionnaire. Data analysis with chi-square test.  Results: Body length and exclusive breastfeeding are related to the incidence of stunting at PMB Midwife S Jakarta in 2022.  Discussion: Based on the results of the analysis related to the incidence of stunting, namely body length and exclusive breastfeeding (p-value = 0,000) while birth weight is not related to the incidence of stunting (p-value = 0,088).